Green start-ups and the role of founder personality - Gary Chapman; Hanna Hottenrott (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
Green start-ups play a vital role in the needed transition towards more environmentally sustainable economies. Yet our understanding of why some founders start green ventures and others do not remains incomplete. We build on the cognitive and decision-making perspectives on start-ups proenvironmental engagement to shed light on the role of founders' personality traits - focusing on the 'Big 5' and risk tolerance - in explaining whether founders' start new ventures with environmentally friendly products. Our analysis of a large, representative, manufacturing and service sector sample of German start-ups illustrates the important role of founder personality traits. Specifically, openness and extraversion promote environmentally friendly products while neuroticism inhibits it. We discuss the implications of these insights.
Keywords: G24; L26; O25; O31; 330; emission reduction; environmentally friendly products; green innovation; Big Fivepersonality traits; sustainability